Genomic analysis of the population structure in horses of the Brazilian Mangalarga Marchador breed - dos Santos, Bruna A. [UNESP]; Pereira, Guilherme L. [UNESP]; Bussiman, Fernando de O.; Paschoal, Victória R. [UNESP]; de Souza Júnior, Sérgio M. [UNESP]; Balieiro, Júlio César de C.; Chardulo, Luís Artur L. [UNESP]; Curi, Rogério A. [UNESP] (Elsevier, 2019)
The Mangalarga Marchador is the Brazilian saddle horse. It has two characteristic gaits, marcha batida and marcha picada, that provide greater comfort to the rider during cavalcade and work. This horse breed is mainly used for work on beef cattle farms and different modalities of equestrian sports. The objective of this study was to characterize the linkage disequilibrium (LD), calculated by r², of Brazilian Mangalarga Marchador horses raised in Brazil using large-scale SNP genotyping. We also investigated the effective size (Ne) of the population, as well as its structure and relationships. A total of 240 Mangalarga Marchador horses of both sexes, registered with the Brazilian breeders association (ABCCMM), were used. The number of informative SNPs was 377,308. Principal component analysis showed that Mangalarga Marchador horses of the two different gait types belong to the same population, i.e., these groups did not segregate significantly within the breed. This finding should be taken into consideration in genetic population studies. The estimated genomic r² was 0.096 ± 0.166. The LD declined considerably at distances greater than 15 and 20 kb, with values lower than 0.3 and 0.2, respectively. The current Ne was 99 animals. There was a marked reduction in this parameter when the estimated Ne of 16 generations ago was considered, which was 650 animals. These results may be linked to a broad and partially open genetic base and to increasing selection pressures in the breed. Finally, we observed defined population substructures that were more related to the breed's important sires rather than to the type of gait.
Keywords: Effective size; Linkage disequilibrium; Population structure; SNP